Soil-Site Suitability Evaluation for Wheat in Calcareous Basaltic Soils of Girnar Toposequence in Southern Saurashtra Region of Gujarat - and S.G. Savalia, Gopal Gandhi (Journal of the Indian Society of Soil Science, 2016)
The five representative pedons were evaluated for their suitability to wheat in the soils of different land slopes of Girnar toposequence of Southern Saurashtra region of Gujarat. The soils of pedon P3 belonging to Typic Haplustert are suitable for wheat cultivation, whereas the soils of pedon P4 belonging to Typic Haplustepts and pedon P5 belonging to Typic Ustifluvents are currently not suitable for wheat cultivation. The soils of pedon P1 and P2 belonging to Lithic Ustorthents and Lithic Haplustepts are not suitable for wheat cultivation. Topography, texture, shallow soil depth, high CaCO3, drainage and salinity are major limitations in the soils of Girnar toposequence of Southern Saurashtra. Results showed that the suitability classes can be improved if the correctable limitations (soil fertility characteristics) are altered through soil amelioration measures.